Relationships between characteristics of the spine-pelvis system and feet in boys aged 7 to 13 years - Mirosław Mrozkowiak; Marek Sokołowski (Kazimierz Wielki University, 2016)
Mrozkowiak Mirosław, Sokołowski Marek. Relationships between characteristics of the spine-pelvis system and feet in boys aged 7 to 13 years. Journal of Education, Health and Sport. 2016;6(5):177-192. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51450 http://ojs.ukw.edu.pl/index.php/johs/article/view/3520   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 14.05.2016.     Relationships between characteristics of the spine-pelvis system and feet in boys aged 7 to 13 years   1Mirosław Mrozkowiak, 2Marek Sokołowski   1Bioergonsport, Nowa Biała 8p, 09-411 Biała 2Akademia Wychowania Fizycznego, ul. Królowej Jadwigi 27/39, Poznań     Keywords: spatial characteristics of body trunk and feet.   Abstract Introduction. Process of formation of physiological curvatures and foot arch should be considered spatially and with regard to several-level biokinetic chain formed by spine, pelvis and lower limbs. Huge variability and mutual relationships of parameters that describe this chain results from the effect of various stressors. Material and Method. 7,509 observations were obtained in the study from urban (5,033 or 67.02%) and rural areas (2,476 or 32.97%). Observations focused on 104 characteristics of the spine and pelvis system in individual age categories. In order to assess these parameters, the authors used a system for computer analysis of body posture that is designed based on the phenomenon of projection moire. Results. Statistical analysis revealed that among characteristics of pelvis and spine, the correlations with characteristics of feet are observed for: differences in the distance of inferior angles of the scapulae from spinous processes measured horizontally along the straight lines; angle of body inclination to the right in the frontal plane and maximum deviation of spinous process of the vertebra to the right. Furthermore, characteristics of feet which are most frequently correlated with parameters of pelvis-spine system are: fifth toe hallux valgus angle and toe varus deformity angle in the right feet. Conclusions 1. Mutual relationships between characteristics of feet and spine-pelvis system are incidental and random. 2. No regularities and logical relationships were found between the parameters of the pelvis-spine system and feet. No mutual effect on each other can be observed and the only observation is their coexistence.